Bouveret’s syndrome: presentation of two cases with review of the literature and development of a surgical treatment strategy - Nickel, Felix; Müller-Eschner, Matthias; Chu, Jackson; Tengg-Kobligk, Hendrik von; Müller, Beat P. (BMC surgery, 2013)
Bouveret’s syndrome causes gastric outlet obstruction when a gallstone is impacted in the duodenum or stomach via a bilioenteric fistula. It is a rare condition that causes significant morbidity and mortality and often occurs in the elderly with significant comorbidities. Individual diagnostic and treatment strategies are required for optimal management and outcome. The purpose of this paper is to develop a surgical strategy for optimized individual treatment of Bouveret’s syndrome based on the available literature and motivated by our own experience.